Antimicrobials resistance patterns and the presence of stx1, stx2 and eae in Escherichia coli - AssumpÇÃo, Gustavo Lacerda Homem; Cardozo, Marita Vendovelli; Beraldo, Lívia Gerbase; Maluta, Renato Pariz; Silva, Joviany Talita; Avila, Fernando Antonio De; Mcintosh, Douglas; Rigobelo, Everlon Cid (UFBA - Universidade Federal da Bahia, 2015)
The objectives of this study were to investigate whether antimicrobial resistance (AMR) or the presence of resistance genes was associated with the occurrence of the virulence genes, stx1, stx2 andeae. Three virulence genes and 11 AMR phenotypes were examined using polymerase chain reaction (PCR) and antimicrobial susceptibility tests. From 800 samples collected in this study, 561 samples were isolatesE. coli strains , being: 90 (16.0%) carriers ofstx1, 97 (17.3%) of stx2 and 45 (8.0%) ofeae genes singly. Thirty seven (6.6%) isolates were carriers of stx1 and stx2, 110 (19.6%) were carriers of stx1 and eae and 67 (11.9%) were carriers of stx2 and eae. The most common virulence gene detected was stx1followed bystx2. The findings showed no relationship between presence of virulence factors and antimicrobial resistance. Also was not found relationship between serogroup and virulence factors.

Objetivou-se com este estudo investigar se a resistência antimicrobiana (RAM) ou a presença de genes de resistência foi associada com a ocorrência dos genes de virulência, stx1, stx2 e eae e os sorogrupos deEscherichia coli isoladas a partir de vacas-vacas leiteiras. Três genes de virulência e 11 fenótipos RAM foram examinados através de PCR e testes de susceptibilidade aos antimicrobianos. Das 800 amostras colhidas neste estudo, 561 amostras foram isoladas cepas de E. coli, sendo: 90 (16,0%) portadoras de stx1, 97 (17,3%) de stx2 e 45 (8,0%) dos genes eae, separadamente. Trinta e sete (6,6%) isolados foram portadores de stx1 e stx2, 110 (19,6%), foram portadores destx1 e eae e 67 (11,9%) foram portadores de stx2 e eae. O gene de virulência mais comum detectado foi stx1 seguido por stx2. O sorogrupo predominante entre os isolados portadores de stx1 foi O119. Entre as cepas portadoras de stx2, eae e também estirpes com nenhum fator de virulência, o sorogrupo predominante foi O9. O RAM dos isolados, medido fenotipicamente, não foi associado com a presença ou ausência de genes de virulência na população saudável de vaca leiteira-nem a sua ocorrência a qualquer um dos sorogrupos foi associada com genesstx1 e stx2 e eae.
Padrões de resistência antimicrobianos e da presença de stx1, stx2 e eae em Escherichia coli
Keywords: antimicrobial resistance; dairy cow; Escherichia coli; serogroups; STEC; Escherichia coli; resistência antimicrobiana; sorogrupos; STEC; vaca leiteira